Professional English language course with content - Chowdhury, Samina Nasrin (BRAC University, 2010)
This paper offers a critical examination of a content-based professional EFL course, designed by centre for Languages (CFL), BRAC University in Bangladesh with the objectives of improving students’ language skills, content knowledge and professional attitude. How content-based instruction (CBI) develops students’ language and cognitive learning are analyzed in Bangladesh EFL context with literature review. The out come shows progress in students’ language proficiency as well as their professional knowledge. A brief outline of the course with implementation process are also presented with the aim of focusing CBI as an effective way for creating motivated, enthusiastic and better learners.